CONCEPTUAL BLENDING IN HOUSE M.D. - Cichmińska, Monika; Topolewska, Marta (Acta Neophilologica, 2011)
The purpose of the present paper is to show how conceptual metaphor theory and blending theory or conceptual integration model can be complementary in analysis of language. We are going to discuss the language of the medical television series House M.D. (seasons 1-5) with the aim to demonstrate how the use of conceptual metaphors and blends reveals the mysterious workings of the human body, disease, diagnosis and treatment to laymen - the viewers. The article discusses six examples of blending paying special attention to the following features of blending operations: achieving goals of blending, namely providing human scale, global insight and coming up with a story, and inputs clashing.